Universal Health Coverage Implementation: A Comparative Policy Review Based on WHO and World Bank Reports - Ilham Kurniawan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Universal Health Coverage (UHC) has become a central objective of global health governance, yet significant variation persists in how countries interpret and implement its policy architecture. This study examines how implementation pathways are constructed and evaluated within major global policy reports, focusing on analytical frameworks developed by leading international health and development institutions. Using a non-empirical qualitative policy review design, the research analyzes institutional reports published between 2015 and 2025 alongside comparative scholarly literature on financing, governance, and service delivery. Documents were examined through thematic coding and comparative discourse analysis to identify how coverage, financial protection, quality of care, and governance are framed as reform priorities. Findings indicate that global monitoring systems tend to emphasize measurable financial indicators and insurance expansion, while empirical research highlights governance coordination, primary health care capacity, and adaptive policy learning as more decisive for equitable and sustainable outcomes. The study concludes that global evaluation frameworks function not only as assessment tools but also as normative instruments shaping national reform agendas. Reframing monitoring approaches toward systemic integration may strengthen the effectiveness of future UHC strategies.